Теоретичні основи стратегічного маркетингу підприємства - Шквиря, Наталя Олександрівна; Шквыря, Наталья Александровна; Shkvyria, Natalia (My University, 2020)
UK: У статті розглянуто теоретичні основи стратегічного маркетингу підприємства. Узагальнено наукові засади сутності економічної категорії «стратегічний маркетинг» та розкрито організаційно-економічні особливості використання стратегічного маркетингу в системі управління підприємством. Зазначено, що стратегічний маркетинг являє собою процес оцінки впливу зовнішніх чинників, вибір стратегічної позиції на ринку з урахуванням цілей і розроблення моделей адекватного реагування на вплив зовнішніх і внутрішніх чинників із метою розроблення стратегічних рішень, що забезпечують цільову позицію на ринку. Основними елементами системи стратегічного маркетингу автором виділено аналітично- планову, функціональну, контролюючу підсистеми. Встановлено, що найважливішим компонентом аналітично-планової підсистеми стратегічного маркетингу на етапах встановлення цілей і ситуаційного аналізу виступає аналіз стратегічної ситуації, в якій знаходиться підприємство. Сформульовано роль стратегічного маркетингу підприємства та визначено принципи його реалізації. RU: В статье рассмотрены теоретические основы стратегического маркетинга предприятия. Обобщены научные основы сущности экономической категории «стратегический маркетинг» и раскрыты организационно-экономические особенности использования стратегического маркетинга в системе управления предприятием. Отмечено, что стратегический маркетинг представляет собой процесс оценки воздействия внешних факторов, выбор стратегической позиции на рынке с учетом целей и разработку моделей адекватного реагирования на влияние внешних и внутренних факторов с целью разработки стратегических решений, обеспечивающих целевую позицию на рынке. В качестве основных элементов системы стратегического маркетинга автором выделены аналитически-плановая, функциональная, контролирующая подсистемы. Установлено, что важнейшим компонентом аналитическо-плановой подсистемы стратегического маркетинга на этапах установления целей и ситуационного анализа выступает анализ стратегической ситуации, в которой находится предприятие. Сформулирована роль стратегического маркетинга предприятия и определены принципы его реализации. EN: In the article the enterprise strategic marketing the theoretical bases are considered. The scientific foundations of the economic category the essence "strategic marketing" are generalized and the organizational and economic features of the use of strategic marketing in the enterprise management system are revealed. It is investigated that the implementation of the modern marketing paradigm is objectively conditioned by the promotion of strategic marketing as the most important function of the enterprise management system. It is stated that strategic marketing is a process of assessing the impact of external factors, the choice of strategic position in the market, taking into account the goals and the development adequate response models to the influence of external and internal factors, in order to develop strategic decisions that ensure the target position in the market. The importance and place of the strategic marketing system as central in the strategic management of the enterprise is substantiated. The principles of strategic marketing are defined: scientific and analytical prediction, accounting and coordination of external and internal factors of development, compliance of tactics and management of the enterprise, certainty of strategy and organization of strategic control. As the main elements of the strategic marketing system, the author has identified the following subsystems: analytical, planned, functional, controlling. It is established that the most important component of the analytical and planning subsystem of strategic marketing in the stages of goal setting and situational analysis is the analysis of the strategic situation in which the enterprise is located. The elements of strategic marketing planning and the methods and models used in this process are identified. It is substantiated that within the system an enterprise strategic marketing the tasks of developing a marketing strategy are solved, including strategic analysis of environment, market, competition and business factors, identifying tendencies of business development, setting goals of the enterprise and its economic units, choice of target market strategies, defining marketing goals and positioning programs. The role of the enterprise strategic marketing is formulated and principles of its realization are defined. Generalized tasks that solve the strategic marketing of the enterprise.
Theoretical foundations of enterprise strategic marketing
Keywords: маркетинг; стратегічний маркетинг; система стратегічного маркетингу; маркетингова стратегія; стратегічний аналіз; стратегія підприємства; маркетинг; стратегический маркетинг; система стратегического маркетинга; маркетинговая стратегия; стратегический анализ; стратегия предприятия; marketing; strategic marketing; system of strategic marketing; marketing strategy; strategic analysis; enterprise strategy